The usage of Case studies and Role-plays in enhancing EFL learners’ Fluency and Critical thinking skills (Texas Journal of Philology, Culture and History, 2024)
This study explores the effectiveness of case studies and role plays as pedagogical tools to enhance English as a Foreign Language (EFL) learners’ fluency and critical thinking skills. Through a mixedmethods approach involving classroom interventions, surveys, and pre- and post-tests, the study investigates how these interactive teaching techniques impact students’ ability to use English in real-life contexts, while also fostering critical thinking. The results suggest that case studies and role plays significantly improve fluency, as learners engage in realistic dialogues and problem-solving activities. Additionally, these methods help develop critical thinking skills, as students analyze scenarios, make decisions, and express opinions. The findings support the integration of these interactive methods into EFL curricula to promote communicative competence and cognitive skills.